Brine, englacial structure and basal properties near the terminus of McMurdo Ice Shelf, Antarctica. Issue 74 (2nd November 2017) - Campbell, S.; Courville, Z.; Sinclair, S.; Wilner, J.
ABSTRACT: We collected ~1300 km of ground-penetrating radar profiles over McMurdo Ice Shelf, Antarctica, using frequencies between 40 and 400 MHz to determine extent, continuity and depth to the brine. We also used profiles to determine meteoric ice thickness and locate englacial features, which may suggest ice shelf instability. The brine extends 9–13 km inland from the ice shelf terminus and covers the entire region between Ross, White and Black Islands. Jump unconformities and basal fractures exist in the brine and ice shelf, respectively, suggesting prior fracturing and re-suturing. One 100 MHz profile, the most distal from the ice shelf edge while still being situated over the brine, simultaneously imaged the brine and bottom of meteoric ice. This suggests a negative brine salinity gradient moving away from the terminus. The meteoric ice bottom was also imaged in a few select locations through blue ice in the ablation zone near Black Island. We suggest that brine, sediment-rich ice and poor antenna coupling on rough ice attenuates the signal in this area. When combined with other recent mass-balance and structural glaciology studies of MIS, our results could contribute to one of the most high-resolution physical models of an ice shelf in Antarctica.